Clarification of succinic acid fermentation broth by ultrafiltration in succinic acid bio–refinery. Issue 3 (11th May 2012) - Wang, Caixia; Li, Qiang; Tang, Huang; Zhou, Wei; Yan, Daojiang; Xing, Jianmin; Wan, Yinhua
Abstract BACKGROUND: Succinic acid is an important precursor chemical for the synthesis of high value‐added products. In this work, ultrafiltration was first investigated to clarify succinic acid fermentation broth by integrating fermentation and separation and removal processes of the product in situ. Four different ultrafiltration membranes (PES 100 kDa, PES 30 kDa, PES 10 kDa and RC 10 kDa) were used in this work. RESULTS: Results indicate that ultrafiltration is feasible for clarifying succinic acid fermentation broth. Almost all the microorganism cells (99.6%) were removed from the fermentation broth. Proteins were also removed effectively by all the membranes studied. The removal rate was 79.86% for PES 100 kDa, 86.43% for PES 30 kDa, 86.83% for PES 10 kDa, and 80.06% for the RC 10 kDa. After ultrafiltration, a clearer permeate was obtained compared with that from centrifugation. CONCLUSION: Membranes operating at high flux are always susceptible to rapid fouling. Compared with molecular weight cut‐offs (MWCO), membrane material has a significant influence on the flux. Membrane flux measured in this study shows industrial potential of this technology in treatment of succinic acid fermentation broth. © 2012 Society of Chemical Industry